Penipuan (Ghisy) dalam Jual Beli: Analisis Hadis tentang Etika Perdagangan Islam - Reski Eka Putri; Muhammadiyah Amin; Abdul Rahman Sakka (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
This study examines the practice of fraud (ghisy) in buying and selling transactions within traditional markets and online marketplaces. Ghisy, linguistically meaning deception or concealing defects, is strictly prohibited in Islam as affirmed by the Prophet Muhammad's saying: "Whoever cheats is not one of us" (HR. Muslim). This research aims to identify three main forms of fraud in trade: concealing product defects, altering product facts (tahrif description), and cheating in measurements and false oaths. Employing a qualitative library research method, this study analyzes primary sources from canonical hadith collections (Shahih Bukhari, Shahih Muslim, Sunan Ibnu Majah) and secondary sources from contemporary Islamic legal literature on commercial ethics. The findings reveal that all three forms of fraud remain prevalent in both traditional and digital marketplaces, causing significant consumer losses and eroding Islamic commercial ethics. Additionally, the study identifies contributing factors including weak regulatory oversight, low trader awareness, and insufficient verification practices by buyers. This research concludes that every trader is obligated to uphold honesty in transactions, while buyers must exercise vigilance and conduct thorough verification before completing payments. The study recommends strengthening oversight mechanisms and enhancing Islamic ethical education for traders to combat commercial fraud effectively.